Traffic Accidents and Their Implications on the Balance of Family Rights and Obligations from the Perspective of Maqashid Sharia (Case Study of the Pulau Taliabu Police Department) - Edi Jain Nurhasa; Jubair Situmorang; Harwis Alimuddin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the impact of traffic violations, particularly red light violations, on the balance of rights and responsibilities within the family from the perspective of maqashid syariah. The research was conducted in Pulau Taliabu Regency using a descriptive qualitative approach. Data were collected through in-depth interviews with victims’ families, traffic officers, and community leaders, as well as documentation from related institutions. The findings reveal that traffic violations have serious implications for family life, especially when the victim is the head of the household or primary breadwinner. These impacts include economic disruption, changes in household roles, and psychological stress on family members. In the maqashid syariah perspective, such violations indicate neglect of the protection of life (hifz al-nafs), property (hifz al-mal), and lineage (hifz al-nasl). Therefore, addressing traffic violations requires a multidimensional approach: legal enforcement, public education, and the internalization of religious values in traffic behavior.